The lean journey of the finnish real estate. - Merikallio, Lauri (Revista Ingeniería de Construcción, 2023)
Nothing teaches us more than our experiences. That was the main reason why the Finnish construction industry has not only studied Lean and IPD but also launched several pilot projects by public owners to learn, adapt Lean principles in practice, and develop an IPD model suitable for the Finnish construction industry. The IPD model demands teamwork and adapting Lean and IPD industrywide is also teamwork. In Finland, several owners and service providers have been working together since 2010 sharing their learnings in workshops, seminars, and conferences. Over 100 IPD projects have also been a platform for several academic papers. The Finnish Universities have published tens of master’s and doctoral theses during the past 10 years on Lean construction, IPD, and alliance models. The Finnish construction industry has gained major benefits and made important progress on its Lean journey. Lean philosophy and tools have delivered tangible cost savings in projects and services and improved cost estimates, schedule adherence, quality, integration, and collaboration in construction projects. Finland has succeeded in creating smooth and practical discussion and development forums that have shaped the whole industry. The key drivers contributing to this progress are collaboration and integration, confidence-building between the partners as well a deeper understanding and application of the Lean principles in construction. As a result, Lean and integrated project execution are already reflected in the strategies adopted by many companies and client organizations.